2019
DOI: 10.21767/2473-6457.10026
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of Fe, Mn and Cu in the tissues of two fish species from lake Qarun, Egypt

Abstract: The current investigation aimed to determine the accumulated levels of heavy metals (Fe, Mn and Cu) in fish (T. zilii and M. capito) organs (muscles, liver and gill) collected from different sites of Lake Qarun in four seasons (August 2014 to May 2015. Metal concentrations in fish species tissues from the eastern part of the lake followed an abundance of: Fe>Mn>Cu. However, metal concentrations from the middle and west of the lake followed an abundance of: Fe>Cu>Mn. Tissues showed different capacities for acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…The MPI of the total combination of metals revealed that metal concentrations in gills, liver, and muscles varied seasonally, with a greater MPI for fish taken in the summer. These results are supported by Ibrahim and Omar [66] and Mohamed et al [67].…”
Section: Heavy Metal Bioaccumulation and Metal Pollution Index In Sol...supporting
confidence: 85%
“…The MPI of the total combination of metals revealed that metal concentrations in gills, liver, and muscles varied seasonally, with a greater MPI for fish taken in the summer. These results are supported by Ibrahim and Omar [66] and Mohamed et al [67].…”
Section: Heavy Metal Bioaccumulation and Metal Pollution Index In Sol...supporting
confidence: 85%
“…It may also provide an early warning signal in stressed organism [15]. Different concentrations of heavy metals were accumulated in the liver of T. zillii and M. capito collected from different sites of Lake Qarun [16]. In the current study, ALT and AST activities decreased significantly (p ≤ 0.05) compared to the control value in the liver of T. zillii and M. capito collected from different sites of the lake.…”
Section: Discussionmentioning
confidence: 42%